DEFORMABILITY AND SHEAR STRENGTH PARAMETERS OF THE FOUNDATION OF A PROJECT ON TANJERO FORMATION IN IRAQ USING RMR AND GSI - ALSHKANE, YOUNIS M. ALI (Journal of Duhok University, 2021)
Determination of the shear strength and deformability parameters of weak rocks are very significant in order to design the foundation of buildings on it economically and safely. Tanjero formation consists of an alternation of sandstone and silty marlstone and it is considered as a weak rock layer which makes it difficult to determine precisely its bearing capacity. Understanding the behavior of this formation under loading is one of the most challenges in geotechnical engineering. The formation underlies most of the areas in Sulaimani city and significant projects such as Shari Daik and Barzayakni Sulaimni projects in Sulaimani city in Iraq. In this paper, the mentioned parameters of this formation were predicted and recommended for the foundation of a multi-story building at Shari Daik project in Sulaimani city in Iraq based on Rock Mass Rating (RMR) and Geological Strength Index (GSI) rock systems.